Intermittent cycles of remote ischemic preconditioning augment diabetic foot ulcer healing. Issue 2 (March 2015) - Shaked, Gad; Czeiger, David; Abu Arar, Anwar; Katz, Tiberiu; Harman‐Boehm, Ilana; Sebbag, Gilbert
ABSTRACT The morbidity and mortality caused by diabetic foot ulcer (DFU) are still significant. Conservative treatment of DFU is often ineffective. Treatment modalities using stem cells directly into the DFU or systematically have been introduced recently. Ischemic preconditioning (IPC) has been proved to be a cheap, simple, and safe method which can augment stem cells number in the peripheral blood circulation. This study's purpose was to test whether IPC can improve DFU healing. Forty diabetic patients were enrolled and divided into study and control groups. All patients received their regular treatment. The study group patients received in addition brief, transient cycles of IPC while the control group patients received a sham procedure only. The procedure was repeated every 2 weeks to complete a follow‐up period of 6 weeks. The ulcers were photographed to measure wound area, and the degree of granulation tissue was assessed. No serious adverse events were noted. Twenty‐two patients from the study group and 12 from the control group completed the entire follow‐up. The ratio of patients who reached complete healing of their ulcer was 9/22 (41%) in the study group compared with 0/12 (0%) in the control group, p = 0.01. Furthermore, the mean remaining ulcer area at the end of the follow‐up was significantly smaller in the study group, 25 ± 6% of the initial area vs. 61 ± 10% in the control group, p = 0.007. The degree of granulation increased after one cycle of treatment in 8/24 (33%) study patients compared to 3/16 (19%) in the control group, p = 0.47. Remote, repeated IPC significantly improves the healing of DFU. This simple, safe, inexpensive treatment method should be considered to be routinely applied to diabetic patients with DFU in addition to other regular treatment modalities.